Sistematización de la experiencia del montaje Rent, el musical en inglés en el curso teatro contemporáneo 2019 (2021)
This degree project systematizes the experience of the Contemporary Theater course of the Bachelor of Arts Education program with an emphasis on Dance and Theater at the Antonio Nariño University during the academic period 2019 - 1, for the understanding of the stage assembly process of the work Rent, by the musical theater in English and thus identify the didactic strategies used in the course.